Study of CO2 adsorption time for carbonate species and linear CO2 formations onto bimetallic CaO/Fe2O3 by infrared spectroscopy - Azizul Hakim Lahuri; Mohd Ambar Yarmo (Penerbit Universiti Kebangsaan Malaysia, 2022)
The CO2 adsorption time for carbonate species and linear CO2 formation onto bimetallic CaO/Fe2O3 was investigated. The total basicity for CaO/Fe2O3was 52.85 cm3g-1 which is located at a medium basic site with maximum CO desorption temperature at 454 ℃. The CO2 adsorption was conducted by using a fluidized bed reactor at 4, 12, 24 and 36 h. The element distribution on the adsorbent showed carbonate formation through an increment of the C element when the CO2 adsorption time was longer. At 4 h of CO2 adsorption, the adsorbent is capable of generating bicarbonate, monodentate carbonate and bidentate carbonate species. The vibrational modes of the physisorbed linear CO2 for CO2 absorbed product at the absorption region of 2240-2402 cm-1 was identified after 36 h of CO2 adsorption. The absorption bands were assigned according to the adjacent CO2 molecule interactions giving formation of the core layer and second layer linear CO2 on the CaO/Fe2O3 surfaces. The results of the present work show that the addition of CaO on the Fe2O3 surfaces enhanced the basic site of the adsorbent which could generate several carbonate species and CO2 adsorbed products at ambient condition.